2019
DOI: 10.3390/molecules24162963
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemistry Insight into the Interactions Between Deep Eutectic Solvents and SO2

Abstract: A systematic research work on the rational design of task specific Deep Eutectic Solvents (DES) has been carried out via density functional theory (DFT) in order to increase knowledge on the key interaction parameters related to efficient SO2 capture by DES at a molecular level. A total of 11 different DES structures, for which high SO2 affinity and solubility is expected, have been selected in this work. SO2 interactions in selected DES were investigated in detail through DFT simulations and this work has gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 80 publications
1
19
0
Order By: Relevance
“…Cao et al indicated that the formation of HB between HBA and HBD enhanced the CO 2 solubility in DESs (Cao et al, 2015). In addition, Atilhan et al investigated the interactions between DES and SO 2 by the quantum chemistry, confirming a dominant VdW interaction between DES and SO 2 (Atilhan et al, 2019). These findings support our results.…”
Section: Excess Enthalpy Predictionsupporting
confidence: 90%
“…Cao et al indicated that the formation of HB between HBA and HBD enhanced the CO 2 solubility in DESs (Cao et al, 2015). In addition, Atilhan et al investigated the interactions between DES and SO 2 by the quantum chemistry, confirming a dominant VdW interaction between DES and SO 2 (Atilhan et al, 2019). These findings support our results.…”
Section: Excess Enthalpy Predictionsupporting
confidence: 90%
“…Negative values of Δ G rxn can be used to indicate the thermodynamical feasibility. Previously, B3LYP and M062X have been used in the simulation of ChCl-based DESs [ 35 38 ]. In Table 1 , Δ G rxn values of easily obtained DESs were lower than 0, according to the Δ G rxn results of B3LYP ( ).…”
Section: Resultsmentioning
confidence: 99%
“…Excessive addition of Tween80 could however complicate the compositions and affect the biocompatibility of hydrolysates in biobutanol fermentation. At 0.5% Tween80, the total sugar reached 53.8 g L −1 , which was adequate for butanol fermentation [38]. As a result, addition of 0.5% Tween80 is selected for the hydrolysis of pretreated corncob into fermentable sugars.…”
Section: Development Of Fed-batch Pretreatment Processmentioning
confidence: 99%
“…Negative values of ΔG rxn can be used to indicate the thermodynamically feasibility. Previously, B3LYP and M062X have been used in the simulation of ChCl based DESs [31][32][33][34]. In Table 1, ΔG rxn values of easily obtained DESs were lower than 0, according to the ΔG rxn results of B3LYP (ΔGB3LYP rxn).…”
Section: Synthesis Of Dessmentioning
confidence: 98%